ASSESSMENT OF THE MICROBIOLOGICAL QUALITY OF THE RIVER GOMATI AT JAUNPUR (U.P.) INDIA: Life Science-Environmental sciences - KUMAR SINGH, PRAMODA; KUMAR SINGH, ARVIND (International Journal of Life Science and Pharma Research, 2014)
The Gomati river in Jaunpur was investigated for its pollution status over a period of one year during June 2009 and May 2010. The sampling is concerned from upstream to downstream regions of the river through the city. Five sampling sites namely : Kalichabad Ghat (Control Site). Gular Ghat (Site I), Hanuman Ghat (Site II), Baluwa Ghat (Site III) and Miyanpur Ghat (Site IV) were selected for sampling. The bacteriological analysis of the river water samples included bacteriological parameters like Total Coliform Count (TC), Faecal Coliform Count (FC) and Faecal Streptoccal Count (FS). Total Coliform Count of river was observed lower at control site than that of the other sites. MPN values ranged from a minimum 875/100 mL at the control site in the month of February and March to a maximum 98×103 /100 mL at site-I in the month of July. Total Coliform bacterial count at all the sites, except the control, was beyond the prescribed limit indicating polluted condition of river Gomati. Faecal Coliform and Faecal Streptococci counts were recorded lower at the control site and higher at other experimental sites. This indicates the higher discharge of faecal organic content of the experimental sites.